Jesus of Nazareth, the Mountain of the Lord: Isaiah 2, Messianism, and the “Lifted Up” Christ of the Fourth Gospel - Ferda, Tucker S. (Novum Testamentum, 2025)
This article identifies and traces an overlooked exegetical tradition of reading Isa 2’s vision about the future exaltation of Zion in a messianic key. It suggests that the Gospel of John is part of this reception history. In the climactic utterance of 12:32 (“And when I am lifted up from the earth, I will draw all people to myself”), John identifies the upcoming death and resurrection of Jesus with the expected “lifting up” of the mountain of the Lord’s house, where the nations will stream to worship at the end of days. The paradoxical theologia crucis of the Fourth Gospel emerges as a species of Second Temple Jewish messianism.